Transmission electron microscopic evaluation of neuronal changes in methylmercury-exposed zebrafish embryos (Danio rerio). (1st November 2016) - Hassan, Said A.; Farouk, Sameh M.; Abbott, Louise C.
ABSTRACT: Our work aimed to elucidate the ultrastructural changes associated with brain neurons in wild-type zebrafish embryos exposed to different concentrations of methylmercury. Zebrafish embryos were exposed to one of five concentrations of methylmercury (0 [negative control], 5, 10, 50, and 80 parts per billion) starting at six hours post fertilization (hpf). At 96 hpf, cells in the zebrafish embryo brains were examined using transmission electron microscopy. The developing neurons of the control embryos sowed normal cellular ultrastructure. Few alterations were observed among the neurons of zebrafish embryos exposed to 5 ppb methylmercury. The cells of the embryos exposed to 10 ppb methylmercury showed slight cellular degeneration as demonstrated by the accumulation of electron dens bodies which were presumably lysosomes in different stages of formation. In embryos exposed to 50 ppb methylmercury, the neuronal cytoplasm conained large electron dense lysosomes and the rough endoplasmic reticulum appeared to be reduced and irregular in shape. Furthermore, the embryonic brain neurons exposed to 80 ppb methylmercury showed the most severe ultrastructural changes, including some that were consistent with different stages of the cell death process. Obvious cellular changes were observed in this highest exposure group included: disrupted or degenerating nuclei; fragmentation or vacuolization of mitochondrial cristae; and loss of mitochondrial matrix density. Based on these observations, we conclude that these different morphological patterns of cellular changes may reflect either different stages of the cell death process or different types of cell death due to 24 hours of exposure to 80 ppb methylmercury.